DESign of Sustainable One-Pot Chemoenzymatic Organic Transformations in Deep Eutectic Solvents for the Synthesis of 1,2-Disubstituted Aromatic Olefins - Ríos-Lombardía, Nicolás; Rodríguez-Álvarez, María Jesús; Morís, Francisco; Kourist, Robert; Comino, Natalia; López-Gallego, Fernando; González-Sabín, Javier; García-Álvarez, Joaquín (Frontiers in Chemistry, 2020)
The self-assembly of styrene-type olefins into the corresponding stilbenes was conveniently performed in the Deep Eutectic Solvent (DES) mixture 1ChCl/2Gly under air and in the absence of hazardous organic co-solvents using a one-pot chemo-biocatalytic route. Here, an enzymatic decarboxylation of p-hydroxycinnamic acids sequentially followed by a ruthenium-catalyzed metathesis of olefins has been investigated in DES solvent. Moreover, and to extend the design of chemoenzymatic processes in DESs, we also coupled the aforementioned enzymatic decarboxylation reaction to now concomitant Pd-catalyzed Heck-type C-C coupling to produce biaryl derivatives under environmentally friendly reaction conditions.